UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA PEMBELAJARAN BUSY BOOK PADA MATA PELAJARAN IPAS DIKELAS IV MIN 11 KOTA MEDAN - Herdika Fauzan Ginting; Pangulu Abdul Karim; Nirwana Anas (JOURNAL SAINS STUDENT RESEARCH, 2025)
The research conducted is entitled "EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH BUSY BOOK LEARNING MEDIA IN SCIENCE SUBJECTS IN CLASS IV MIN 11 MEDAN CITY" and is based on the phenomenon that student learning outcomes in science subjects are relatively concerning. Students are less interested in science subjects and consider natural and social sciences to be boring, unpleasant subjects, and face-to-face activities in class are limited to listening to lectures and reading. In fact, the curriculum requires that the skills acquired involve higher-order thinking, similar to analysis. Busy Book is a learning tool in the form of an activity book equipped with games, and learning materials in each design to involve students in learning and increase student learning outcomes in science subjects. The research methodology uses a type of classroom action research. The research population was students at MIN 11 Medan City with a sample of 25 students in the group. The aim of the research was to determine whether or not there was an increase in student learning outcomes after using the busy book. Based on research conducted in class IV MIN 11 Medan City, the use of Busybook Media turned out to deliver significant results on student learning outcomes in science subjects. This can be seen through the average score of student learning outcomes using Busybook media, which is 84.4. Meanwhile, the pre-test results before using the busy book showed that the average student received a score of 63.6, which is still below the KKM (Minimum Completeness Criteria).